2020
DOI: 10.1155/2020/9343475
|View full text |Cite
|
Sign up to set email alerts
|

Both Low and High Postprocedural hsCRP Associate with Increased Risk of Death in Acute Coronary Syndrome Patients Treated by Percutaneous Coronary Intervention

Abstract: Background. Inflammation poses dual effects after myocardial infarction, but robust evidence shows that high-sensitivity C-reactive protein (hsCRP), as an inflammatory marker, is constantly associated with worse outcomes. This study is aimed at investigating the probable nonlinear association between postprocedural hsCRP and mortality in patients with acute coronary syndromes (ACS) treated by percutaneous coronary intervention (PCI). Methods. A total of 3940 consecutive ACS patients treated by PCI with postpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Robust evidence (22)(23)(24) has shown that levels of inflammation markers, including hs-CRP and Ddimer, are constantly associated with worse mortality among patients with ACS who underwent PCI. Our previous study (25) revealed that during a median follow-up of 727 days, both low and high post-procedural hs-CRP levels were associated with a higher risk of death in patients with ACS who underwent PCI. Hs-CRP is the key marker of the interleukin (IL)-1β/IL-6/CRP pathway to synthesize and recruit leukocyte after myocardial damage (26).…”
Section: Post-procedural Inflammation Level and Renal Function Are Asmentioning
confidence: 97%
“…Robust evidence (22)(23)(24) has shown that levels of inflammation markers, including hs-CRP and Ddimer, are constantly associated with worse mortality among patients with ACS who underwent PCI. Our previous study (25) revealed that during a median follow-up of 727 days, both low and high post-procedural hs-CRP levels were associated with a higher risk of death in patients with ACS who underwent PCI. Hs-CRP is the key marker of the interleukin (IL)-1β/IL-6/CRP pathway to synthesize and recruit leukocyte after myocardial damage (26).…”
Section: Post-procedural Inflammation Level and Renal Function Are Asmentioning
confidence: 97%
“…In this study, we found that hsCRP levels were not associated with MACE risk ( P = 0.077), which may be because we selected the median level of hsCRP as the cutoff while the cutoff was 2 or 3 mg/L to assess residual cardiovascular risk in most previous studies 11,34 . Besides, our previous study found that both low and high hsCRP levels were associated with increased risk of death in AMI patients, 12 which may partially explain that no significance in the median levels of hsCRP and MACE risk in this study. In addition, we observed that TMAO levels were negatively correlated with hsCRP levels ( P = 0.009), which is consistent with the result of the previous study 35,36 .…”
Section: Discussionmentioning
confidence: 72%
“…High‐sensitivity C‐reactive protein (hsCRP), a systemic inflammatory response marker, is extensively used to evaluate inflammatory risk in patients with myocardial infarction (MI) 10–12 . Some studies have suggested that TMAO may activate the inflammation cascade 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-sensitivity C-reactive protein (hsCRP), as a marker of systemic inflammation, has been proven to be associated with increased relative risks of cardiovascular events in patients with coronary stenting. 27,28 In this study, compared with the non-CI-AKI group, the level of hsCRP in the CI-AKI group was significantly increased, and hsCRP was closely related to the incidence of CI-AKI. Liu et al demonstrated that the increase in hsCRP level is a significant and independent predictor of CI-AKI in STEMI patients treated with primary PCI, and those with higher hsCRP were associated with in-hospital mortality and composite MACEs closely related.…”
mentioning
confidence: 54%